Introduction: [Chinese perceptions of Russia and the West : changes, continuities and contingencies during the twentieth century] - Müller-Saini, Gotelind (Chinese perceptions of Russia and the West, 2020)
The introduction outlines the main ideas behind this book, its genesis, and the relationship with extant scholarship. Before presenting a tour through the book, it discusses the different viewpoints on Russia and its relation to Europe or “the West” as articulated in “the West” and in Russia herself as a background for studying the Chinese views on the topic. Since the latter were also intertwined with Japan to some degree, the role and impact of Japanese perceptions of Russia and “the West” are also briefly recalled. Similarly, the concept of “the West” itself is not a set and fixed given, but needs to be problematized. The book’s main aim consists of looking closer into the changes, continuities, and contingencies of Chinese perceptions of Russia and the West during the JSth century, focusing on three areas: official normative views as reflected in Chinese school history textbooks; creative imaginary approaches in literature; and visual and material manifestations in everyday life. Acknowledging “Greater China” as representing “Chinese” perceptions, beyond mainland China also Taiwan, and to some degree Hong Kong and Macau, are addressed. Taking the JSth century with its many historical shifts and reconfigurations of entities in political, social, and economic terms as the longitudinal line, the book presents a multilayered discussion of “Chinese” perceptions of what “Russia” and “the West” meant for whom, when, and why; where “frontlines” between them were acknowledged; and under which circumstances, by whom, and to which end, the entities as such were constructed, questioned, reconfigured, merged, or even dissolved.